The Effect of Halal Label Awareness and Word of Mouth (WOM) on Attitude toward Halal Product and Consumer Purchase Decision of Solaria Restaurant in Pontianak - galih, Galih Seni Rupawan B12112017 (Jurnal Manajemen Update, 2017)
This research aimed to determine the effect of halal label awareness and word of mouth (WOM) on purchase decision through attitude toward halal product as a mediator variable and Solaria Restaurant in Pontianak as the research object. Because lately when we talked about halal, it is no longer just purely a religious issue. It is becoming a global symbol for quality assurance and lifestyle choice in the realm of business and trade. This research is quantitative serves to test the hypothesis proposed in the research and answered the problem in the research. The sample of this research is muslim consumers in Pontianak age 17 – 60 years old, who has knowledge about solaria halal issues and concern about halal food. The data are obtained by using questionnaire. This research uses random sampling, which total sample is 150, and SmartPLS 3.0 to process the data. The hypothesis of the research is H1: Halal label awareness has positive influence to attitude toward halal product, H2: WOM has positive influence to attitude toward halal product, H3: Halal label awareness has positive influence to purchase decision, H4: WOM has positive influence to purchase decision and H5: Attitude toward halal product has positive influence to purchase decision. H6: Halal label awareness has direct influence to purchase decision through attitude toward halal product, H7: WOM has direct influence to purchase decision through attitude toward halal product. The result of this research shows that H1, H3 and H4 are accepted but H2, H5, H6 and H7 are rejected.Keyword : Halal Label Awareness, WOM, Attitude toward Halal Product, Purchase Decision